Genetics of resistance to Sesamia inferens infestation and its correlation with yield in maize. Issue 4 (10th June 2015) - Sekhar, Javaji C.; Karjagi, Chikkappa G.; Kumar, Bhupender; Rakshit, Sujay; Soujanya, Lakshmi; Kumar, Pradyumn; Singh, Krishan P.; Dhandapani, Appavoo; Dass, Sain; Kumar, Ramanujam S.; Lübberstedt, T.
Abstract Sesamia inferens (Walker) causes 25.7–78.9% losses in maize production in South and South‐East Asia. The genetic basis of host plant resistance is the prerequisite for resistance breeding. Twenty‐four populations derived from S. inferens resistant × susceptible inbreds were used to study the genetic regulation of resistance to S. inferens in maize, to determine the importance of genetic effects through generation mean analysis (GMA) and to understand correlation between resistance and yield. Resistant and susceptible inbreds differed significantly in leaf and stem injury ratings (LSIR), a measure of host plant resistance. Mean LSIR range among resistant and susceptible parents was 2.15–2.55 and 7.83–8.22, respectively. The broad‐sense heritability ranged from 0.40 to 0.71, and the mean number of effective factors ranged from 1.9 to 2.6. The resistance against S. inferens was largely governed by additive × additive (i), followed by dominance (d) and additive (a) gene effects. Significant negative correlation (−0.27 to −0.96) was observed between LSIR and yield. The findings suggest reciprocal recurrent selection for development of new inbreds with resistance followed by their involvement in hybrid development to exploit additive and non‐additive gene effects/variance.